Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a)\(\frac{1}{4}.x=-\frac{1}{3}\)
\(x=-\frac{1}{3}:\frac{1}{4}\)
\(x=-\frac{4}{3}\)
b)\(-\frac{3}{7}+x=\frac{5}{8}\)
\(\text{ }x=\frac{5}{8}-\left(-\frac{3}{7}\right)\)
\(x=\frac{59}{56}\)
c)\(\frac{16}{2^x}=2\)
\(2^x=\frac{16}{2}\)
\(2^x=8\)
\(\Rightarrow2^x=2^3\)
vậy x=3
\(x^2-\frac{100}{36}=0\) \(=>x^2=\frac{100}{36}\)
\(=>x=\frac{10}{6}\)hoặc\(x=\frac{-10}{6}\)
Mà x > 0
Nên \(x=\frac{10}{6}\)
a, Ta có : \(-\dfrac{3}{2}-2x+\dfrac{3}{4}=-2\)
\(\Rightarrow-2x=-2+\dfrac{3}{2}-\dfrac{3}{4}=-\dfrac{5}{4}\)
\(\Rightarrow x=\dfrac{5}{8}\)
Vậy ...
b, Ta có : \(\left(-\dfrac{2}{3}x-\dfrac{3}{5}\right)\left(-\dfrac{3}{2}-\dfrac{10}{3}\right)=\dfrac{2}{5}\)
\(\Rightarrow-\dfrac{29}{6}\left(-\dfrac{2}{3}x-\dfrac{3}{5}\right)=\dfrac{2}{5}\)
\(\Rightarrow-\dfrac{2}{3}x-\dfrac{3}{5}=-\dfrac{12}{145}\)
\(\Rightarrow-\dfrac{2}{3}x=-\dfrac{12}{145}+\dfrac{3}{5}=\dfrac{15}{29}\)
\(\Rightarrow x=-\dfrac{45}{58}\)
Vậy...
Giải:
\(-\dfrac{52}{100}:x=\dfrac{9,36}{1658}\)
\(\Leftrightarrow x=-\dfrac{52}{100}:\dfrac{9,36}{1658}\)
\(\Leftrightarrow x=-\dfrac{829}{9}\)
Vậy \(x=-\dfrac{829}{9}\).
Chúc bạn học tốt!